PENDUGAAN UMUR SIMPAN BIJI KOPI ROBUSTA DENGAN PENDEKATAN KADAR AIR KRITIS - Pertiwi, Made Gendis Putri; Nofrida, Rini; Anggraini, Ines Marisya Dwi; Afriansyah, Dilla; Rahayu, Olivia; Zainuri, Zainuri; Rahayu, Novia; Utama, Qabul Dinanta (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2024)
Post-harvest handling techniques on coffee beans determine the quality of coffee beans in terms of physical, sensory, and microbiological quality. Drying and storage are two critical points that play an important role in determining the water content in green beans. This study aimed to predict the shelf life of green bean stored using critical moisture content approach. The green beans stored at various humidity (RH 32%, 56%, 68%, 75%, 84%). Furthermore, sample was determinated the critical moisture content, equilibrium moisture content, and estimation of shelf life. The Accelerated Shelf Life Test (ASLT) method with the critical moisture content approach was used to predict the shelf life of robusta green coffee beans. The results showed that the critical moisture content value of coffee beans was 0.147 g H2O/g solid and the equilibrium moisture content was reached on day 10. The Guggenheim-Anderson-de Boer (GAB) mathematical model is closest to the experimental conditions so it was chosen to be used in determining the Aw value when the critical moisture content is reached. Based on the calculation results, the shelf life of coffee with metallized plastic packaging is 11.3 months at 68% RH.